Studi Kebutuhan Bahan Baku Industri Pengolahan Ikan Skala Mikro di Kabupaten Mojokerto - Miftakhul Ulumiah; Mochammad Amin Alamsjah; Patmawati Patmawati (Universitas Mataram, 2024)
The availability of raw materials in an industry is very important to prevent supply shortages, so that business continuity can be guaranteed. This condition can also affect the fixed costs that must be borne, especially if the production process stops.The aim of this research is to determine the amount of raw materials needed by the micro-scale fish processing industry in Mojokerto Regency. The research method used survey and interview methods with 18 respondents in the micro-scale fish processing industries in Mojokerto Regency. The research was conducted for 30 days and data analysis used quantitative descriptive. The results of the research show that the dominant fish used as raw material for fish processing is mackerel. The highest amount of raw material needed for mackerel fish occurred in 2022 at 753,864 kg and the highest amount of stock shortage reached 53,668 kg in 2020. The wader fish commodity has been fulfilled every year with the highest amount of raw material needed at 33,348 kg in 2023, while the catfish commodity has also been fulfilled. every year with the highest amount of raw material requirements in 2023 amounting to 27,421 kg.